CONCEPTUALIZATION OF INCLUSIVE EDUCATION AND LEGAL GUARANTEES IN UZBEKISTAN - Sitora Kadirova (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2020)
The article examines the understanding of inclusive education. Its various functions and principles are analyzed, as well as the role of individualization of learning in general. The article highlights a number of key issues related to teaching in an inclusive environment. Legal ways to increase the role of inclusive education for children with special needs are identified